Sentinel Lymph Node Biopsy Vs Pelvic Lymphadenectomy In Early-Stage Endometrial Cancers: Feasibility, Safety and Lymphatic Morbidity - Saeed, Saira; Gul, Uzma; Urooj, Uzma; Khan, Sumaira (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare sentinel lymph node biopsy (SLNB) and pelvic lymphadenectomy (PLND) in early-stage endometrial cancers in terms of feasibility, operative outcomes, lymphatic and other complications.Study Design: Quasi experimental study.Place and duration of study: Department of Obstetrics and Gynecology, Combined Military Hospital (CMH), Rawalpindi, Jun 2023 to Jun 2025Methodology: This study retrospectively analyzed 28 women, with histologically confirmed, early stage (I-II) endometrial cancer, who had undergone complete surgical staging. Using Technetium 99 and blue dye, 16 patients had undergone sentinel lymph node biopsy whereas 12 patients had pelvic lymphadenectomy. Both groups were compared in terms of demographics, tumor characteristics, operative factors, postoperative outcomes including length of hospital stay, incidence of postoperative infection and lower limb lymphedema. Patients were followed up for 30 days post-surgery.Results: Mean age of patients was 56.07±6.57 years. There was no significant difference between the groups regarding demographics and tumor characteristics (p>0.05). Endometrioid adenocarcinoma was the most common histology (85.70%). Mean operative time was significantly shorter in the sentinel lymph node biopsy group as compared to pelvic lymphadenectomy (125.80 ± 44.00 vs 247.90 ± 48.40 min, p 0.05).Conclusion: Sentinel lymph node biopsy in early-stage endometrial cancer is associated with significantly shorter operative time and a lower incidence of lower limb lymphedema compared with pelvic lymphadenectomy, making it a feasible alternative that